Balmes y el criterio para filosofar (Anuario Filosófico, 2018)
The method of philosophizing is connected with all the man phaculties. As well with the truth, which is captivated three ways: the conscience, the evidence and the “common sense”. The objective affirmation of the truth has five dangers: fanaticism, intolerance, lack of dialogie, rumination and twisting of thought. To achieve the truth involves defeating three obstacles: passions, selfishness and laziness. Balmes propose three ways to blat them: thinking, humbleness and strength of will. So the mishod requires understanding will and sentiment.